Penerapan Dynamic Governance untuk Meningkatkan Pelayanan Publik dalam Pembangunan Zona Integritas Menuju WBBM di BBPMP Jatim. - Jihan Nabilah Adinda Putri; Bambang Kusbandrijo; Supri Hartono (Universitas 17 Agustus 1945 Semarang, 2025)
Bureaucratic reform in Indonesia is a key focus of the government to improve the quality of public services that are effective, efficient, and accountable. This study aims to analyze the implementation of Dynamic Governance in the development of the Integrity Zone at the East Java Provincial Education Quality Assurance Agency. The method used is a descriptive qualitative approach, which allows for a deep understanding of the perspectives of employees and the community. The findings indicate that the application of the elements of Thinking Ahead, Thinking Again, and Thinking Across in Dynamic Governance can improve public services at the East Java Provincial Education Quality Assurance Agency. However, there are still challenges in employees' understanding of the concept of the Integrity Zone and resistance to change. The implications of this study highlight the importance of training and socialization to enhance employees' understanding, as well as cross-sectoral collaboration in achieving the goals of a clean and service-oriented Integrity Zone. This research is expected to contribute to the development of a more adaptive and responsive governance model that addresses community needs.